A comprehensive review of database resources in chemistry - Sauban Ghani, Syed (Eclética Química, 2020)
As scientific community worldwide is publishing a huge number of research articles in various fields; it is necessary to distinguish between databases that are efficient and objective for literature searches. This review offers information on the important points of the database. None of the databases are complete and perfect, but they complement each other. If a library can only afford one, choice must be based on the priorities of institutional needs. The benefits that databases can provide in the preparation of the literature review for developing future studies and dissemination of research are discussed. This paper provides an overview of the most frequently used free chemistry databases such as PubChem, Crystallography Open Database, PubMed, ZINC, ChemSpider, and Google Scholar. It also gives a brief description of three major commercial databases such as Scopus, Web of Science, and SciFinder. Thus, substance and citation databases that covers almost all areas of chemistry, has become an invaluable tool in bibliometric analysis.